Dynamic adjustment towards target capital structure: Thailand evidence - Haron, Razali; Ibrahim, Khairunisah; Mat Nor, Fauzias; Ibrahim , Izani (Universiti Kebangsaan Malaysia, 2013)
By employing panel data, the present study examines the dynamic aspects of capital structure of 269 non-financial listed firms in Thailand from 2000 to 2009. This is a relatively new area in finance literature. The present study investigates the existence of target capital structure, speed of adjustment and factors affecting the speed of adjustment. The analyses are conducted using the dynamic Partial Adjustment Model (PAM) and estimated based on the Generalized Method of Moments. The results indicate the existence of target capital structure and firms undergone adjustment processes to be at their target capital structure from time to time with a considerably rapid speed of adjustment, consistent with the dynamic trade-off theory. Firms in Thailand are found to be under-adjusting, being below the required adjustment to be at the target within a year. Strong evidence exists that indicates that firm specific factors significantly influence speed of adjustment for firms in Thailand, such as distance from target, size of firm and profitability.